Iridoid glycosides from the fruits of Cornus officinalis. Issue 10 (3rd October 2018) - Wang, Xin; Liu, Chong-Hui; Li, Jin-Jie; Zhang, Bo; Ji, Lin-Lin; Shang, Xiao-Ya
Abstract: Four new iridoid glycosides named cornusphenosides A–D (1–4) were isolated from an ethanol extract of the fruits of Cornus officinalis (shan zhu yu). The structures of these compounds were elucidated on the basis of spectroscopic data (UV, IR, HRESIMS, and 1D and 2D NMR) and chemical evidence. The neuroprotective effects of compounds1–4 were also assessed in vitro .